Desain Antarmuka Berbasis Pengguna pada Aplikasi Komik Mobile: Studi Kasus pada Aplikasi NanoComic - Amanda, Naurah Adinda Putrie; Astuti, Luh Gede (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2024)
NanoComic is an online platform that enables users to read comics online. The purpose of this research is to design a user interface and user experience based on mobile devices, aligning with the increasing interest in reading comics nowadays. The method employed in this study is the system usability scale, which is used to measure the extent to which the system can be easily used from the subjective perspective of users through the completion of Likert-scale questionnaires. Consequently, this application is expected to address the existing issues within the community.